The climate of the city and its ecological significance - Auelbekova, A.Zh.; Kystaubayeva, Z.T.; Onayev, S.T.; Kurmangaliyeva, D.S. (KSU Publ., 2011)
Literature review on natural-climatic conditions of urban areas is conducted in this article. Environmental assessment of urban areas is given. Natural and climatic environment of urban areas continues to lose its quality that makes it not only uncomfortable, but also dangerous to public health. Loss of quality of urban environment is associated not only with an extremely high level of physical-chemical air pollution, but also with noise, vibration and other anthropogenic impacts. These impacts on the surface layer of the atmosphere adversely affect the health of the population that uses urban areas both for recreation and for a walk or for other purposes.
Қала климаты жəне оның экологиялық маңыздылығы
Keywords: environment; population; health; the climatic conditions; temperature; weather; desertification; area; urban lifestyle; сreation